2016
DOI: 10.1175/jcli-d-15-0636.1
|View full text |Cite
|
Sign up to set email alerts
|

Homogenization and Assessment of Observed Near-Surface Wind Speed Trends across Sweden, 1956–2013

Abstract: Multidecadal variability of observed near-surface wind speed from 24 stations across Sweden has been analyzed for 1956–2013, with a focus on 1979–2008 (incorporating an additional 9 stations) for comparison with previous studies. Wind speed data have been subjected to a robust data processing protocol, consisting of quality control, reconstruction, and homogenization, by using geostrophic wind speed series as reference. The homogenized dataset displays a significant (at p < 0.05) downward trend for 1956… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
96
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(104 citation statements)
references
References 44 publications
8
96
0
Order By: Relevance
“…Coastal locations exhibited higher wind speeds than interior stations in all months of the year, with maximum monthly wind speeds occurring in the winter months. Minola et al (2016) found similar results. Figure 7 shows the spatial distribution of trends in annual and seasonal time series based on the raw and adjusted monthly mean wind speed.…”
Section: Variance Comparison Before and After Adjustmentsupporting
confidence: 62%
See 4 more Smart Citations
“…Coastal locations exhibited higher wind speeds than interior stations in all months of the year, with maximum monthly wind speeds occurring in the winter months. Minola et al (2016) found similar results. Figure 7 shows the spatial distribution of trends in annual and seasonal time series based on the raw and adjusted monthly mean wind speed.…”
Section: Variance Comparison Before and After Adjustmentsupporting
confidence: 62%
“…Accordingly, to obtain the best results, here the monthly candidate and its reference series in the calendar order were transformed into series in a calendar year with the same month; this technique has not been used in previous studies on the homogenization of near-surface wind speed (Wan et al 2010;Li et al 2011;Cusack 2013;Minola et al 2016;Azorin-Molina et al 2014, 2016. The change signal in the climate time series may be a systematic error, but it may also be a periodic variation in local climate (Li 2016).…”
Section: Creation Of the Reference Seriesmentioning
confidence: 99%
See 3 more Smart Citations